2008
DOI: 10.1158/1535-7163.mct-07-0573
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs modulate the chemosensitivity of tumor cells

Abstract: MicroRNAs are strongly implicated in such processes as development, carcinogenesis, cell survival, and apoptosis. It is likely, therefore, that they can also modulate sensitivity and resistance to anticancer drugs in substantial ways. To test this hypothesis, we studied the pharmacologic roles of three microRNAs previously implicated in cancer biology (let-7i, mir-16, and mir-21) and also used in silico methods to test pharmacologic microRNA effects more broadly. In the experimental system, we increased the e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
229
2
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 328 publications
(241 citation statements)
references
References 41 publications
9
229
2
1
Order By: Relevance
“…24 In addition, inhibition of miR-21 has been shown to increase the sensitivity of NCI60 and cholangiocarcinoma cell lines to chemotherapeutic agents. 17,25 miR-20b is highly overexpressed in ESCC and gastric cancer, 26,27 and its high-expression level is associated with a lower probability of survival. 28 The expression of miR-205 is highly specific for squamous epithelium, 29 and it has been shown to be downregulated in both esophageal adenocarcinoma and ESCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 In addition, inhibition of miR-21 has been shown to increase the sensitivity of NCI60 and cholangiocarcinoma cell lines to chemotherapeutic agents. 17,25 miR-20b is highly overexpressed in ESCC and gastric cancer, 26,27 and its high-expression level is associated with a lower probability of survival. 28 The expression of miR-205 is highly specific for squamous epithelium, 29 and it has been shown to be downregulated in both esophageal adenocarcinoma and ESCC.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13] Altered expression of miRNAs in primary human cancers has been used for tumor diagnosis, classification, staging and prognosis. 14 Furthermore, the involvement of miRNAs in the response of tumor cells to chemotherapeutic agents has also been confirmed, [15][16][17] which suggests that miRNAs could have a broad effect on the response of cancer cells to chemotherapy.…”
Section: Introductionmentioning
confidence: 90%
“…The regulation of the other two major multidrug resistance transporters, Pglycoprotein/MDR1 and MRP1, by miR-451, -27a and -326, respectively, have also been reported (Kovalchuk et al, 2008;Liang et al, 2010). More importantly, modulation of miRNA expression or function can alter sensitivity of cancer cells to anticancer drugs (Zhu et al, 2008;Pan et al, 2009;Blower et al, 2008). This could be achieved by inhibiting the function of up-regulated miRNAs or restoring the expression of down-regulated miRNAs.…”
Section: Microrna-mediated Regulation Of Abcg2mentioning
confidence: 95%
“…First, miRNA expression is largely dysregulated in drug-resistant cancer cells (Zhu et al, 2008;Pan et al, 2009). Second, the miRNA expression patterns in the NCI-60 drug screen cell lines are significantly correlated to the sensitivity patterns of the cancer cells for a large set of anticancer agents (Blower et al, 2008). Third, numerous miRNAs have been found to regulate drug resistance genes such as DHFR (Mishra et al, 2007) and BCL2 (Xia et al, 2008).…”
Section: Microrna-mediated Regulation Of Abcg2mentioning
confidence: 99%
“…Thus, miRNAs were confirmed to modulate breast cancer initiation, invasion and metastasis (24)(25)(26). At present, several studies have suggested the importance of miRNAs in modulating the chemosensitivity and chemoresistance of tumor cells (27)(28)(29). Si et al reported that suppression of miR-21 sensitized MCF-7 cells to topotecan (30) and enhanced chemosensitivity of leukemic HL60 cells to arabinosylcytosine (31).…”
Section: Introductionmentioning
confidence: 99%